THE STRUCTURE OF SHORT-DISTANCE RUNNING - Rade Stefanović; Ljubiša Lilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In order to determine estimation of current sprinter-s ability, the control is necessary on the track while measuring passing times, at every five or ten meters. With these results one can determine what parts of certain races are suitable for a sprinter. Having these data, the trainer is planning and making programs for training process with the help of adequate training methods and means. The basic precondition for a regular training work is testing of all four phases: the start, acceleration, running up the lane phase and the finish. Generally speaking, all sprinters don't have the same dynamics taking in consideration all these phases, which means that a good sprint starter isn't necessarily good at the finish. One of the facts is that in practice one should use the least possible the numbers of phase testing but on the other hand he should be much more informed.